Effect and process evaluation of a kindergarten-based, family-involved cluster randomised controlled trial in six European countries on four- to six-year-old children's steps per day: the ToyBox-study - Marieke De Craemer; Maïté Verloigne; Ilse De Bourdeaudhuij; Odysseas Androutsos; Violeta Iotova; Luis Moreno; Berthold Koletzko; Piotr Socha; Yannis Manios; Greet Cardon; on behalf of the ToyBox-study group (BMC, 2017)
Abstract Background The ToyBox-intervention is a theory- and evidence-based intervention delivered in kindergartens to improve four- to six-year-old children's energy balance-related behaviours and prevent obesity. The current study aimed to (1) examine the effect of the ToyBox-intervention on increasing European four- to six-year-old children' steps per day, and (2) examine if a higher process evaluation score from teachers and parents was related to a more favourable effect on steps per day. Methods A sample of 2438 four- to six-year-old children (51.9% boys, mean age 4.75 ± 0.43 years) from 6 European countries (Belgium, Bulgaria, Germany, Greece, Poland and Spain) wore a motion sensor (pedometer or accelerometer) for a minimum of two weekdays and one weekend day both at baseline and follow-up to objectively measure their steps per day. Kindergarten teachers implemented the physical activity component of the ToyBox-intervention for 6 weeks in total, with a focus on (1) environmental changes in the classroom, (2) the child performing the actual behaviour and (3) classroom activities. Children's parents received newsletters, tip cards and posters. To assess intervention effects, multilevel repeated measures analyses were conducted for the total sample and the six intervention countries separately. In addition, process evaluation questionnaires were used to calculate a total process evaluation score (with implementation and satisfaction as a part of the overall score) for teachers and parents which was then linked with the physical activity outcomes. Results No significant intervention effects on four- to six-year-old children' steps per weekday, steps per weekend day and steps per average day were found, both in the total sample and in the country-specific samples (all p > 0.05). In general, the intervention effects on steps per day were least favourable in four- to six-year-old children with a low teachers process evaluation score and most favourable in four- to six-year-old children with a high teachers process evaluation score. No differences in intervention effects were found for a low, medium or high parents' process evaluation score. Conclusion The physical activity component of the ToyBox-intervention had no overall effect on four- to six-year-old children' steps per day. However, the process evaluation scores showed that kindergarten teachers that implemented the physical activity component of the ToyBox-intervention as planned and were satisfied with the physical activity component led to favourable effects on children's steps per day. Strategies to motivate, actively involve and engage the kindergarten teachers and parents/caregivers are needed to induce larger effects.